The Effect of Good Corporate Governance and Financial Performance on Islamic Social Reporting Disclosure: Evidence from Sharia Banks Registered with the Financial Services Authority (OJK) - Siska Noviyanti (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of Good Corporate Governance (GCG) and financial performance on Islamic Social Reporting (ISR) disclosure in Islamic Commercial Banks registered with the Financial Services Authority (OJK) for the 2016-2020 period. This study uses a quantitative approach with secondary data in the form of annual reports from 10 Islamic Commercial Banks over five years, resulting in 50 analysis units. The analytical method used is multiple linear regression. The results show that simultaneously, the size of the Board of Directors, Board of Commissioners, Sharia Supervisory Board, profitability, and leverage significantly influence ISR disclosure. Partially, the size of the Board of Directors and Sharia Supervisory Board has a significant positive effect on ISR disclosure, while the size of the Board of Commissioners, profitability, and leverage have no significant effect. These findings suggest that internal governance mechanisms, particularly the role of the Board of Directors and Sharia Supervisory Board, are more influential in determining the extent of ISR disclosure than financial performance. The practical implication of this research is that Islamic banking management needs to strengthen the effectiveness of its governance structure, particularly by optimizing the role of the Board of Directors and the Sharia Supervisory Board, to improve the quality and breadth of ISR disclosure. Strengthening ISR disclosure is important not only to meet accountability and transparency requirements but also to enhance stakeholder trust, institutional reputation, and the competitiveness of Islamic banks.